Impacts of oil palm on employment, demography and gender issues in Kalangala - Bigirwa, J.; Anena, S.; Katunguka, G. (Ecological Trends Alliance Texts, 2019)
The main aim for introducing oil palm in Uganda’s Lake Victoria islands has been to improve livelihoods through income generation. However, this has only been seen as positive for a small group while many other impacts on pertinent social issues related to employment, demography and gender negatively affected local livelihoods.